Magnesium alloy double-layer composite coating and preparation method and application thereof
By preparing a double-layer composite coating on a magnesium alloy, the problem of insufficient corrosion resistance of magnesium alloy is solved, comprehensive wrapping and protective effects are achieved, and the corrosion durability and protective performance of magnesium alloy are significantly improved.
Patent Information
- Application Number
- CN202510069916.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In applications, magnesium alloys have insufficient corrosion resistance due to their low electrode potential and susceptibility to corrosion, which limits their industrial applications. The prior art has limitations in improving the corrosion resistance of magnesium alloys, especially the coating prepared by hydrothermal method still has defects in its encapsulation properties and cannot fully cover the edges and corners of the sample.
A double-layer composite coating was prepared on a magnesium alloy by hydrothermal method. By polishing and chamfering on the magnesium alloy substrate, and hydrothermal treatment was carried out at 180°C to 200°C to form an Mg(OH)2 coating and a CaSiO3/CaCO3 composite coating to achieve comprehensive wrapping and protective effects.
This method significantly improves the corrosion durability of magnesium alloy, can effectively suppress the corrosion of magnesium alloy, reduce corrosion current, significantly enhance the protective performance of the coating, and has good application prospects.
Smart Images

Figure CN119843277A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloys, and in particular to a magnesium alloy double-layer composite coating and a preparation method and application thereof. Background Art
[0002] Magnesium alloy is an important lightweight material. With its high strength, excellent thermal conductivity, good damping and shock absorption performance and excellent biocompatibility, it has broad application prospects in aerospace, electronic equipment, and biomedicine. However, its low electrode potential and susceptibility to corrosion severely limit its industrial application. At present, the main methods to improve the corrosion resistance of magnesium alloys are alloying, surface modification and surface coating technology.
[0003] Surface coating technology is one of the important ways to improve the corrosion resistance of magnesium alloys. By preparing a coating on the surface of magnesium alloys, the contact between corrosive media and the alloy surface can be effectively blocked, oxidation and corrosion can be delayed, and the corrosion resistance of the alloy can be significantly improved. The coating acts as a protective barrier by isolating the alloy from direct contact with air and moisture. Common coating preparation techniques include micro-arc oxidation, magnetron sputtering, electrodeposition, vapor deposition and hydrothermal method. Among them, the hydrothermal synthesis method is regarded as a promising method for in-situ synthesis of corrosion-resistant coatings because of its economy, environmental protection and high efficiency.
[0004] In recent years, hydrothermal method has made significant progress in the preparation of corrosion-resistant coatings on magnesium alloys. For example, Farasat Iqbal et al. deposited magnesium phosphate coatings by a one-step hydrothermal method, which significantly improved the corrosion performance. Huanlin Zhang et al. successfully prepared hydroxyapatite / lauric acid composite coatings on AZ31 magnesium alloys, and proved that the corrosion resistance of the composite coatings was significantly enhanced by electrochemical measurements of simulated body fluid (SBF) and long-term corrosion resistance tests. Jing Yuan et al. prepared rGO / Mg(OH)2 composite films on AZ61 alloys by hydrothermal method in an alkaline solution containing deionized water and graphene oxide. The study found that with the increase of GO content in the hydrothermal solution, the corrosion resistance of the composite film first increased and then decreased. However, the coatings prepared by the hydrothermal method still have defects in encapsulation and usually cannot completely encapsulate the samples. The overall encapsulation of the coating is the key to the practical application of magnesium alloys, but this problem is often overlooked in research. In the study, it was found that when the coating thickness increased, the coating at the corners of the sample often could not completely cover the substrate.
[0005] From a practical and economic point of view, metal and alloy coatings are generally not widely used in the corrosion protection of magnesium alloys. This is because it is very difficult to grow metal coatings such as nickel, copper, stainless steel and titanium on the surface of magnesium alloys, and usually requires the use of high-cost technologies such as spraying, magnetron sputtering and laser cladding. In addition, there is a large potential difference between these metal coatings and magnesium alloys, which can easily cause galvanic corrosion, further increasing the risk of corrosion. In comparison, calcium carbonate (CaCO3), as a low-cost mineralized material, has the advantages of pH-sensitive release, wear resistance, compatibility and degradability. CaCO3 is stable under neutral or alkaline conditions and only decomposes in acidic environments, so it shows good potential in the development of long-term corrosion-resistant coatings. In addition, silicates can also quickly form a wollastonite layer on the alloy surface and are often used in the preparation of magnesium alloy coatings. Although CaCO3 and silicates have important research significance as corrosion-resistant coatings, there are currently few studies on the combined application of CaCO3 and silicates in corrosion inhibition. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a magnesium alloy double-layer composite coating and a preparation method and application thereof. The magnesium alloy double-layer composite coating prepared by the present invention has a simple method and the prepared magnesium alloy double-layer composite coating shows good protective application prospects.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] The first object of the present invention is to provide a method for preparing a magnesium alloy double-layer composite coating, comprising the following steps:
[0009] (1) polishing the magnesium alloy substrate to obtain a polished substrate, ultrasonically cleaning the polished substrate with ethanol, and then naturally drying to obtain a treated magnesium alloy substrate;
[0010] (2) Mixing a Na2SiO3 solution and a Ca(HCO3)2 solution to obtain a mixed solution, wherein the concentration of Ca(HCO3)2 in the mixed solution is supersaturated; placing the treated magnesium alloy substrate in the mixed solution, performing a hydrothermal treatment at 180°C to 200°C, and then drying to obtain a double-layer composite coating on the treated magnesium alloy substrate, namely, a magnesium alloy double-layer composite coating.
[0011] Principle description: The magnesium alloy matrix is placed in a mixed solution for hydrothermal reaction. Since Ca(HCO3)2 is in an oversaturated state, the incompletely dissolved Ca(HCO3)2 will precipitate on the sample surface. During the heating process, Ca(HCO3)2 decomposes according to the following reaction formula:
[0012] Ca(HCO3)2=CaCO3+H2O+CO2↑;
[0013] At the same time, the AZ91D substrate undergoes an in-situ film-forming reaction. Due to the high chemical activity of magnesium alloys, they react rapidly in aqueous solution. The reaction formula is as follows:
[0014] Mg+2H2O=Mg(OH)2+H2↑;
[0015] The essence of in-situ film formation on the surface of magnesium alloy is the interaction between α-Mg and OH - The reaction of ions forms a dense Mg(OH)2 film in a high temperature and high pressure environment, which has excellent anti-corrosion effect. In addition, the free Ca in a small amount of dissolved Ca(HCO3)2 2+ Radical ions and SiO3 2+ The ions will react to generate new precipitation, forming a new film protection. The reaction formula is as follows, and finally a double-layer composite coating is obtained.
[0016] Ca 2+ +SiO3 2- =CaSiO3↓;
[0017] The beneficial effects of the present invention are as follows: the present invention develops a double-layer composite coating on a magnesium alloy by a hydrothermal method, forming an overall wrapped structure, which effectively inhibits the corrosion of the magnesium alloy.
[0018] Furthermore, the magnesium alloy substrate in step (1) is chamfered before polishing.
[0019] The beneficial effect of adopting the above further solution is that the chamfering treatment can effectively resist the stress concentration at the corners of the magnesium alloy substrate, achieve full wrapping of the magnesium alloy, and thus significantly improve the corrosion durability of the coating.
[0020] Furthermore, the total concentration of Na2SiO3 and Ca(HCO3)2 in the mixed solution is 40-100 mM.
[0021] The beneficial effect of adopting the above further scheme is that the concentration of the mixed solution directly affects the thickness of the CaCO3 and CaSiO3 composite coating. As the concentration increases, the amount of CaCO3 and CaSiO3 deposited increases. The composite coatings prepared by the solution within the concentration range of the present invention effectively inhibit the corrosion of magnesium alloys.
[0022] Furthermore, the total concentration of Na2SiO3 and Ca(HCO3)2 in the mixed solution is 80 mM.
[0023] The beneficial effect of adopting the above further scheme is that the coating sample prepared at 80mM electrolyte concentration shows the lowest corrosion current and the best anti-corrosion performance.
[0024] Furthermore, the volume ratio of the Na2SiO3 solution to the Ca(HCO3)2 solution is 1-2:1-2; the concentration of the Na2SiO3 solution is 40-100 mol / L; the concentration of the Ca(HCO3)2 solution is 40-100 mol / L.
[0025] Furthermore, the hydrothermal treatment time in step (2) is 50 min to 70 min.
[0026] Furthermore, the drying temperature in step (2) is 90° C. to 110° C., and the drying time is 50 min to 70 min.
[0027] Furthermore, when the treated magnesium alloy substrate is placed in the mixed solution in step (2), the treated magnesium alloy substrate is placed horizontally in the mixed solution.
[0028] The beneficial effect of adopting the above further scheme is that the magnesium alloy substrate is placed horizontally in the mixed solution, there is a vortex in the mixed solution system, most of the precipitates flow with the vortex, and fall on the surface of the magnesium alloy substrate when passing through the magnesium alloy substrate, forming a film / block under high temperature conditions to form a coating with protective properties.
[0029] The second object of the present invention is to provide a magnesium alloy double-layer composite coating, which comprises a Mg(OH)2 coating and a CaSiO3 / CaCO3 composite coating from the inside to the outside.
[0030] The beneficial effects of the present invention are as follows: in the present invention, a Mg(OH)2 coating is first generated in situ on the surface of the magnesium alloy, and then a CaSiO3 / CaCO3 composite coating is wrapped. The corrosion current of the prepared coating sample is reduced by 4 to 5 orders of magnitude, and the magnesium alloy substrate can be completely wrapped. The coating has excellent corrosion durability and shows good protection application prospects.
[0031] Furthermore, the thickness of the composite coating is 50 μm to 1 mm.
[0032] The third object of the present invention is to provide an application of a magnesium alloy double-layer composite coating, and to use the magnesium alloy double-layer composite coating for the protection of magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of the preparation of MCS40 according to Example 1 of the present invention;
[0034] Figure 2are SEM images of embodiments 1 to 4 of the present invention; wherein (a) is a SEM image of MCS40 of embodiment 1 at low resolution; (b) is a SEM image of MCS40 of embodiment 1 at high resolution; (c) is a SEM image of MCS60 of embodiment 2 at low resolution; (d) is a SEM image of MCS60 of embodiment 2 at high resolution; (e) is a SEM image of MCS80 of embodiment 3 at low resolution; (f) is a SEM image of MCS80 of embodiment 3 at high resolution; (g) is a SEM image of MCS100 of embodiment 4 at low resolution; (h) is a SEM image of MCS100 of embodiment 4 at high resolution;
[0035] Figure 3 The XRD spectra and EDS images of Examples 1 to 4 and Comparative Example 1 of the present invention; wherein (a) is the XRD spectra of the surface of Examples 1 to 4 and Comparative Example 1, wherein AZ91D is the AZ91D magnesium alloy matrix of Comparative Example 1, 40mM is MCS40 of Example 1, 60mM is MCS60 of Example 2, 80mM is MCS80 of Example 3, and 100mM is MCS100 of Example 4; (b) is the element proportion on the surface of MCS60 of Example 2; (c) is the EDS image of MCS80 of Example 3; (d) is the weight proportion of C element in MCS80 of Example 3; (e) is the weight proportion of O element in MCS80 of Example 3; (f) is the weight proportion of Mg element in MCS80 of Example 3; (g) is the weight proportion of Ca element in MCS80 of Example 3; (h) is the weight proportion of Si element in MCS80 of Example 3;
[0036] Figure 4 Surface XPS spectrum of MCS60 of Example 2 of the present invention; wherein (a) is the full XPS spectrum; (b) is the high-resolution XPS spectrum of C1s; (c) is the high-resolution XPS spectrum of O1s; (d) is the high-resolution XPS spectrum of Mg 1s; (e) is the high-resolution XPS spectrum of Ca2p; (f) is the high-resolution XPS spectrum of Si 2p;
[0037] Figure 5 The test results of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4 and AZ91D of Comparative Example 1 in 3.5wt% NaCl solution are shown in Figure 1; (a) is the open circuit potential; (b) is the potentiodynamic polarization curve; (c) is the cathode Tafe constant (B a ) and the anode Tafe constant (B c ); (d) corrosion potential (E corr ) and corrosion current density (I corr); (e) Stern-Geary coefficient and polarization resistance (Rp); (f) corrosion rate (V corr );
[0038] Figure 6 The EIS test results of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4 and AZ91D of Comparative Example 1 in 3.5wt% NaCl solution of the present invention are shown in Figure 1; (a) is a Nyquist plot; (b) is a Bode impedance plot; (c) is a Bode phase angle plot; (d) is an equivalent circuit of AZ91D of Comparative Example 1 before the inductive reactance disappears; (e) is an equivalent circuit of Examples 1 to 4;
[0039] Figure 7 This is the equivalent circuit of AZ91D in comparative example 1 after the inductive reactance disappears;
[0040] Figure 8 The fitting curves of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4 and AZ91D of Comparative Example 1 in the EIS test of the present invention are shown in FIG. 1 ; wherein (a) is C eff ; (b) is d eff ; (c) is R total ;
[0041] Fig. 9 The Nyquist diagrams, Bode impedance diagrams, and Bode phase angle diagrams of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4, and AZ91D of Comparative Example 1 after being immersed in 3.5wt% NaCl solution for different time periods; wherein (a) is the Nyquist diagram of AZ91D; (b) is the Bode impedance diagram of AZ91D; (c) is the Bode phase angle diagram of AZ91D; (d) is the Nyquist diagram of MCS40; (e) is the Bode phase angle diagram of MCS40 de impedance diagram; (f) is the Bode phase angle diagram of MCS40; (g) is the Nyquist diagram of MCS60; (h) is the Bode impedance diagram of MCS60; (i) is the Bode phase angle diagram of MCS60; (j) is the Nyquist diagram of MCS80; (k) is the Bode impedance diagram of MCS80; (l) is the Bode phase angle diagram of MCS80; (m) is the Nyquist diagram of MCS100; (n) is the Bode impedance diagram of MCS100; (o) is the Bode phase angle diagram of MCS100;
[0042] Fig.10Optical photographs of MCS40 of Example 1 of the present invention, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4, and AZ91D of Comparative Example 1 after being immersed in a 3.5wt% NaCl solution for different time periods;
[0043] Fig.11 The data graphs are of the immersion test and hydrogen evolution test of MCS40 of Example 1 of the present invention, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4, and AZ91D of Comparative Example 1 in 3.5wt% NaCl solution; wherein (a) is the weight loss curve within 24 hours of the immersion test; (b) is the average rate within 24 hours of the immersion test; (c) is a schematic diagram of the hydrogen evolution test; (d) is the hydrogen release curve and average rate within 24 hours of the hydrogen evolution test; (e) is the average rate within 24 hours of the hydrogen evolution test; (f) is the hydrogen release rate and weight loss within 24 hours of the hydrogen evolution test;
[0044] Fig.12 Surface XPS spectrum of MCS60 of Example 2 of the present invention after immersion for 168 hours; wherein (a) is the full XPS spectrum; (b) is the high-resolution XPS spectrum of C1s; (c) is the high-resolution XPS spectrum of O1s; (d) is the high-resolution XPS spectrum of Mg1s; (e) is the high-resolution XPS spectrum of Ca 2p; (f) is the high-resolution XPS spectrum of Si 2p;
[0045] Fig.13 The sample morphology diagrams and simulation analysis diagrams of Example 2 and Comparative Example 3 of the present invention; wherein (a) is the sample morphology diagram of Comparative Example 3; (b) is the sample morphology diagram of Example 2; (c) is the simulation analysis diagram of Comparative Example 3; (d) is the simulation analysis diagram of Example 2;
[0046] Fig.14 The mechanical analysis diagrams of comparative examples 1 and 2 of the present invention at 190°C; (a) is the mechanical analysis diagram of AZ91D subjected to chamfering treatment in comparative example 2; (b) is the mechanical analysis diagram of AZ91D not subjected to chamfering treatment in comparative example 1;
[0047] Fig.15 The transient structures of Comparative Examples 1 and 2 of the present invention at 190°C; (a) is the total deformation; (b) is the equivalent stress data diagram;
[0048] Fig.16 These are optical photographs of MCS40 of Example 5 of the present invention, MCS60 of Example 6, MCS80 of Example 7, MCS100 of Example 8, and AZ91D of Comparative Example 2 after being immersed in 3.5 wt % NaCl solution for different time periods. DETAILED DESCRIPTION
[0049] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0050] Example 1: Preparation of a magnesium alloy double-layer composite coating
[0051] (1) polishing a 25 mm*25 mm*5 mm AZ91D magnesium alloy substrate using 1000 to 2000 mesh sandpaper to obtain a polished substrate, ultrasonically cleaning the polished substrate with ethanol for 10 minutes, and then naturally drying to obtain a treated AZ91D magnesium alloy substrate;
[0052] (2) Pour 65 mL of a 40 mM mixed solution (Na2SiO3 and Ca(HCO3)2 solution with a concentration and volume ratio of 1:1) into a polytetrafluoroethylene reactor lining, then place the treated AZ91D magnesium alloy substrate horizontally into the polytetrafluoroethylene reactor lining, and perform hydrothermal treatment at 190 °C for 60 min to obtain a corrosion-resistant coating sample. Finally, place the coating sample in a 100 °C oven for 60 min. The preparation process is as follows: Figure 1 As shown, a magnesium alloy double-layer composite coating named MCS40 was obtained.
[0053] Example 2: Preparation of magnesium alloy double-layer composite coating II.
[0054] (1) polishing a 25 mm*25 mm*5 mm AZ91D magnesium alloy substrate using 1000 to 2000 mesh sandpaper to obtain a polished substrate. The polished substrate is ultrasonically cleaned with ethanol for 10 minutes, and then naturally dried to obtain a treated AZ91D magnesium alloy substrate;
[0055] (2) Pour 65 mL of a 60 mM mixed solution (Na2SiO3 and Ca(HCO3)2 solution with a concentration and volume ratio of 1:1) into a polytetrafluoroethylene reactor lining, then place the treated AZ91D magnesium alloy substrate horizontally into the polytetrafluoroethylene reactor lining, and perform hydrothermal treatment at 190 °C for 60 min to obtain a corrosion-resistant coating sample. Finally, place the coating sample in a 100 °C oven for 60 min. The preparation process is as follows: Figure 1 As shown, a magnesium alloy double-layer composite coating named MCS60 was obtained.
[0056] Example 3: Preparation of magnesium alloy double-layer composite coating
[0057] (1) polishing a 25 mm*25 mm*5 mm AZ91D magnesium alloy substrate using 1000 to 2000 mesh sandpaper to obtain a polished substrate. The polished substrate is ultrasonically cleaned with ethanol for 10 minutes, and then naturally dried to obtain a treated AZ91D magnesium alloy substrate;
[0058] (2) Pour 65 mL of a mixed solution with a concentration of 80 mM (Na2SiO3 and Ca(HCO3)2 solution with a concentration and volume ratio of 1:1) into a polytetrafluoroethylene reactor lining, then place the treated AZ91D magnesium alloy substrate horizontally into the polytetrafluoroethylene reactor lining, and perform hydrothermal treatment at 190°C for 60 min to obtain a corrosion-resistant coating sample. Finally, place the coating sample in an oven at 100°C for 60 min. The preparation process is as follows: Figure 1 As shown, a magnesium alloy double-layer composite coating named MCS80 was obtained.
[0059] Example 4: Preparation of magnesium alloy double-layer composite coating
[0060] (1) A 25 mm*25 mm*5 mm AZ91D magnesium alloy substrate was polished using 1000-2000 mesh sandpaper to obtain a polished substrate. The polished substrate was ultrasonically cleaned with ethanol for 10 minutes and then naturally dried to obtain a treated AZ91D magnesium alloy substrate.
[0061] (2) Pour 65 mL of a 100 mM mixed solution (Na2SiO3 and Ca(HCO3)2 solution with a concentration and volume ratio of 1:1) into a polytetrafluoroethylene reactor liner, then place the treated AZ91D magnesium alloy substrate horizontally into the polytetrafluoroethylene reactor liner, and perform hydrothermal treatment at 190°C for 60 min to obtain a corrosion-resistant coating sample. Finally, place the coating sample in a 100°C oven for drying for 60 min. The preparation process is as follows: Figure 1 As shown, a magnesium alloy double-layer composite coating named MCS100 was obtained.
[0062] Example 5: Preparation of magnesium alloy double-layer composite coating
[0063] This embodiment is the same as embodiment 1, the only difference being that in step (1), the AZ91D magnesium alloy substrate is chamfered, and the rest of the preparation process, conditions and raw materials are the same as those in embodiment 1.
[0064] Example 6: Preparation of magnesium alloy double-layer composite coating
[0065] This embodiment is the same as Embodiment 2, the only difference being that in step (1), the AZ91D magnesium alloy substrate is chamfered, and the rest of the preparation process, conditions and raw materials are the same as those in Embodiment 2.
[0066] Example 7: Preparation of magnesium alloy double-layer composite coating
[0067] This embodiment is the same as Embodiment 3, the only difference being that the AZ91D magnesium alloy substrate is chamfered in step (1), and the rest of the preparation process, conditions and raw materials are the same as those in Embodiment 3.
[0068] Example 8: Preparation of magnesium alloy double-layer composite coating
[0069] This embodiment is the same as embodiment 4, the only difference being that in step (1), the AZ91D magnesium alloy substrate is chamfered, and the rest of the preparation process, conditions and raw materials are the same as those in embodiment 4.
[0070] Comparative Example 1: AZ91D magnesium alloy matrix
[0071] This comparative example uses the same AZ91D magnesium alloy substrate as in Example 1 without any treatment.
[0072] Comparative Example 2: AZ91D magnesium alloy matrix
[0073] This comparative example is the same as comparative example 1, the only difference being that in this comparative example, the AZ91D substrate is chamfered.
[0074] Comparative Example 3: Preparation of magnesium alloy double-layer composite coating
[0075] This comparative example is the same as Example 2, the only difference being that in step (2), the treated AZ91D magnesium alloy substrate is vertically placed in a polytetrafluoroethylene reactor lining, and the rest of the preparation process, conditions and raw materials are the same as those in Example 2.
[0076] Comparative Example 4: Preparation of magnesium alloy double-layer composite coating
[0077] This comparative example is the same as Example 6, the only difference being that in step (2), the treated AZ91D magnesium alloy substrate is vertically placed in a polytetrafluoroethylene reactor lining, and the rest of the preparation process, conditions and raw materials are the same as those in Example 6.
[0078] Test Example 1:
[0079] 1. Characterization:
[0080] 1.1 Surface morphology
[0081] The surface morphology of the MCS40, MCS60, MCS80 and MCS100 coatings prepared in Examples 1 to 4 was observed using a field emission scanning electron microscope (SEM, Reglus 8100). Figure 2 shown.
[0082] Depend on Figure 2We can get:
[0083] (1) Figure 2 The surface morphologies of MCS40, MCS60, MCS80, and MCS100 prepared in Examples 1 to 4 are shown respectively. From the low-resolution images, i.e. Figure 2 a. Figure 2 c. Figure 2 e and Figure 2 gIt can be observed that the surface microstructure of the magnesium alloy double-layer composite coating is clearly divided into two layers. The first layer is relatively flat, and the surface scratches are traces left during the grinding process. The second layer presents a disordered granular structure, which is randomly arranged on the first layer. This may be the result of the deposition of CaCO3 particles and the formation of wollastonite / calcium silicate (CaSiO3). In addition, Figure 2 a. Figure 2 c. Figure 2 e and Figure 2 g comparison shows that with the increase of the concentration of the mixed solution, the second layer structure of the magnesium alloy double-layer composite coating tends to be denser.
[0084] (2) High-resolution image display, that is Figure 2 b. Figure 2 d. Figure 2 f and Figure 2 h, it can be seen that when the concentration increases, the outermost layer of the surface is covered by a loose porous flocculent structure. This phenomenon is similar to that of SiO3 2- The increase in Wollastonite / Calexandrite concentration is directly related to the increase in Wollastonite / Calexandrite concentration, which may be a direct manifestation of Wollastonite / Calexandrite covering the sample surface.
[0085] 1.2 Phase composition
[0086] The phase compositions of the AZ91D magnesium alloy substrate of Comparative Example 1 and the magnesium alloy double-layer composite coatings of Examples 1 to 4 were detected by X-ray diffraction (XRD, smartlab9, Rigaku Corporation, Japan). Figure 3 (a) shown.
[0087] Depend on Figure 3 (a) It is possible to obtain:
[0088] Figure 3 (a) shows the XRD patterns of the AZ91D magnesium alloy substrate of comparative example 1 and the surfaces of MCS40, MCS60, MCS 80, and MCS100 of examples 1 to 4. It can be seen that the XRD patterns of the magnesium alloy substrate are mainly composed of Mg phase and a small amount of Mg 12 Al 17 Alloy phase composition. With the increase of the concentration of the mixed solution, the peak intensity of the Mg phase is significantly weakened, and the Mg 12 Al 17The alloy phase peak completely disappeared, while the Mg(OH)2 phase peak was strengthened. In addition, the CaSiO3, aragonite (CaCO3) and calcite (CaCO3) phases also showed an enhanced trend. This indicates that the increase in the concentration of the mixed solution leads to the further formation and encapsulation of the coating on the surface of the AZ91D magnesium alloy substrate.
[0089] 1.3 Surface chemical composition
[0090] The chemical composition of the magnesium alloy double-layer composite coating MCS60 surface of Example 2 was characterized by energy dispersive X-ray spectroscopy (EDS, Bruker, Karlsruhe, Germany). Figure 3 (b) Figure 3 (c) Figure 3 (d) Figure 3 (e) Figure 3 (f) Figure 3 (g) Figure 3 (h) shown.
[0091] Depend on Figure 3 (b)~(h) yield:
[0092] After EDS characterization, Figure 3 (b) is the weight percentage of the five main elements C, O, Mg, Ca and Si on the coating surface of MCS60 in Example 2, Figure 3 (c) to (h) are the distribution of the five elements C, O, Mg, Ca and Si. The results show that the peak intensity of the Mg element is the highest, which indicates the presence of the magnesium matrix and Mg(OH)2. The weight percentage of the O element is the highest, reaching 52.34wt%, which is mainly due to the presence of O in Mg(OH)2, CaCO3 and CaSiO3 in the coating. In addition, the loose microstructure is basically consistent with the distribution profile of C, Ca, O and Si elements, indicating that the main components of the loose microstructure of the second layer are Ca CO3 and CaSiO3. Mg(OH)2 is mainly distributed in the flat area of the first layer.
[0093] 1.4 Chemical composition and valence state
[0094] The chemical composition and valence state of the surface of the magnesium alloy double-layer composite coating MCS60 of Example 2 were characterized by X-ray photoelectron spectroscopy (XPS, Escalab 250Xi, Thermo Fisher Scientific Inc.). Figure 4 shown.
[0095] like Figure 4 As shown:
[0096] Figure 4(a) to (f) show the full XPS spectrum of sample MCS60 and high-resolution XPS spectra of C1s, O 1s, Mg 1s, Ca 2p and Si2p. Figure 4 As shown in (a), the full spectrum clearly shows the presence of five elements: C, O, Mg, Ca and Si, which is consistent with Figure 3 The results of XRD and EDS are consistent. In the fine spectrum, C exists in the form of CC bonds and metal carbonates; O exists in the form of metal carbonates / silicates and metal oxides. Mg shows only one characteristic peak, located at the position of the Mg(OH)2 peak, which indicates that the Mg(OH)2 coating completely covers the surface of the AZ91D magnesium alloy. In addition, CaSiO3 and CaCO3 were observed in the fine spectrum of Ca, while only CaSiO3 was found in the fine spectrum of Si. This further verifies the presence of CaSiO3 and CaCO3 components in the composite coating.
[0097] 2 Electrochemical measurements
[0098] Electrochemical tests of the materials were performed using an electrochemical workstation (CS2350H, CorrTest Instruments Ltd, Wuhan, China) using a standard three-electrode system and 3.5 wt % NaCl solution, where the auxiliary electrode was a platinum electrode and the reference electrode was an Ag / AgCl (saturated potassium chloride) electrode with a working area of 1 cm 2 The MCS40, MCS60, MCS80, MCS100 and AZ91D magnesium alloy substrates of Examples 1 to 4 and Comparative Example 1 are used as working electrodes.
[0099] Before the electrochemical test, each group needs to undergo a 30-minute open circuit potential (OPC) test to reduce the impact of surface instability of each group of materials on the electrochemical test results. The results are shown in Figure 5 (a) shown.
[0100] Depend on Figure 5 (a) It is possible to obtain:
[0101] Figure 5(a) shows the open circuit potential test results, which display the changes in the OCP of AZ91D in Comparative Example 1 and MCS40 in Example 1, MCS60 in Example 2, MCS80 in Example 3, and MCS100 in Example 4 within 1800 seconds. The initial OCP value is due to the penetration process of the test solution into the coating. Subsequently, the stabilization of the OCP value means that the surface state is relatively stable, and the corrosion products enhance the corrosion resistance. The OCP value of AZ91D in Comparative Example 1 gradually increases with the increase of the immersion time and finally stabilizes at about -1.55V. The increase in the OCP value reflects the dissolution of Mg and the formation of corrosion products on the alloy surface, and reaches a dynamic equilibrium. The OCP values of MCS40 in Example 1, MCS60 in Example 2, MCS80 in Example 3, and MCS100 in Example 4 are significantly higher than that of AZ91D, indicating that the coating has excellent anti-corrosion effect. The finally stabilized OCP values are in the order of: AZ91D (-1.55V) < MCS40 (-0.72V) < MCS100 (-0.70V) < MCS60 (-0.68V) < MCS80 (-0.52V). Generally, the coatings prepared at higher electrolyte concentrations usually have higher OCP values, which indicates that the corrosion tendency of these coatings is weaker. However, the OCP value of the coating sample prepared at 100 mM electrolyte concentration is at a lower level, which may be due to the porous defects on its surface.
[0102] 2.1 Potentiodynamic polarization
[0103] The electrochemical tests were carried out at room temperature. The potentiodynamic polarization was scanned from -0.5V to 1.5V at a scanning rate of 1 mV / s, and the potentiodynamic polarization curves were obtained as shown in Figure 5 (b). The potentiodynamic polarization curves are used to evaluate the corrosion resistance. By fitting the potentiodynamic polarization curves, the corrosion potential (E corr ), corrosion current density (I corr ), anodic Tafel constant (B a ), cathodic Tafel constant (B c ), corrosion rate (V corr ), Stern-Geary coefficient (B), and polarization resistance (R p ) of MCS40 in Example 1, MCS60 in Example 2, MCS80 in Example 3, MCS100 in Example 4, and AZ91D in Comparative Example 1 can be obtained to compare the corrosion resistance of Examples 1 - 4 and Comparative Example 1. Among them, the detection and calculation methods of the polarization resistance (R p ) and corrosion current density I corr refer to ASTM G59 - 23, as shown in Table 1 and Figure 5 (b) - Figure 5 (f).
[0104] Table 1
[0105]
[0106]
[0107] From Table 1, Figure 5 (b)~ Figure 5 (f) It is possible to obtain:
[0108] (1) The dynamic potential polarization curves of the MCS40, MCS60, MCS80, MCS100 of Examples 1 to 4 and the AZ91D magnesium alloy matrix of Comparative Example 1 in a 3.5 wt % NaCl solution are shown in FIG. Figure 5 As shown in (b), it can be seen from the figure that with the increase of potential, the corrosion current density of MCS40, MCS60, MCS80 and MCS100 is significantly lower than that of AZ91D, which intuitively shows that the coating samples have better anti-corrosion performance. Figure 5 (c) shows that the cathode and anode slope values of AZ91D magnesium alloy matrix are quite different, while those of MCS40, MCS60, MCS80 and MCS100 are smaller. This is the main reason for the larger Stern-Geary coefficient B of AZ91D magnesium alloy matrix. Figure 5 e).
[0109] (2) From Figure 5 (d) As can be seen from Table 1, the corrosion potential (E corr ) moves in the positive direction, the corrosion current density (I corr ) was reduced by at least three orders of magnitude, indicating that the corrosion resistance of the coating samples was significantly improved. Among them, the corrosion current density (I corr ) are reduced by 5 orders of magnitude. In general, a smaller Stern-Geary coefficient B value and a larger R p Values indicate better corrosion performance. Figure 5 (e) shows that the Stern-Geary coefficient B value of the coating sample is reduced compared with that of the AZ91D magnesium alloy substrate, and R p The Rp values of MCS60, MCS80 and MCS100 coating samples are at the same order of magnitude, among which the value of MCS80 is the largest. At the same time, the corrosion rate of MCS80 coating sample is the lowest ( Figure 5 f). Through the comparative analysis of the above potentiodynamic polarization curve data, it can be clearly concluded that the MCS80 coating sample has the best corrosion performance.
[0110] 2.2 Electrochemical impedance spectroscopy (EIS) test
[0111] (1) Using an electrochemical workstation, EIS tests were performed on AZ91D of Example 1 and MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, and MCS100 of Example 4, respectively. The tests were performed at open circuit potential (OCP), with a sinusoidal voltage amplitude of 5 mV and a frequency range of 100 kHz to 0.01 Hz. Within the frequency range of 0.01 Hz to 100000 Hz, the overall corrosion resistance of AZ91D of Example 1 and MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, and MCS100 of Example 4 was analyzed by EIS results, and Nyquist and Bode plots were obtained. The results are as follows: Figure 6 (a) Figure 6 (b) Figure 6 (c) as shown.
[0112] (2) The impedance spectrum data after testing of AZ91D of comparative example 1, MCS40 of example 1, MCS60 of example 2, MCS80 of example 3, and MCS100 of example 4 were fitted with an equivalent circuit (EEC). The results are as follows: Figure 6 (d) Figure 6 (e) shows that the scattered points in the figure represent the measured data, and the fitted data are shown in the curve. The fitted data of each component are shown in Table 2, and the effective capacitance C is calculated. eff , effective thickness d eff , Total resistance R related to corrosion protection total The results are shown in Table 3. Figure 8 The specific calculation methods of each data are as follows:
[0113] In the fitting circuit of AZ91D, R s (solution resistance), the low frequency region is composed of inductance (L) and resistance (R L ) composition, indicating that the alloy has pitting corrosion. When the surface of AZ91D is coated, the inductance loop disappears. This is because of the defects and heterogeneity of AZ91D. f / R f It represents the constant phase components and corrosion film resistance of the corrosion film, while in the coating sample it is related to the corrosion electrolyte penetration resistance of the coating.
[0114] CPE dl / R ct is the double layer capacitance of the substrate / coating interface and the charge transfer resistance of the substrate / coating.
[0115] CPE i / R i With CPE f / R fThe parallel combination represents the second constant related to the capacitive and resistive response of the dense interior of the coating. The constant phase element (CPE) is used to describe the behavior of an ideal capacitor instead of a pure capacitor. Its impedance is expressed as follows:
[0116]
[0117] Where ω is the angular frequency, j is an imaginary number, Y0 is the CPE admittance, and n is the CPE empirical index. The value of n ranges from 0 to 1, where n = 0 represents pure resistance and n = 1 represents pure capacitance.
[0118] For the evaluation of the double layer capacitance represented by CPE, the changes in Y (constant phase element coefficient) and n related to the oxide layer are used to evaluate the effective capacitance (C eff ) is calculated using the Brug equation, as shown below:
[0119]
[0120] Brug equation evaluates C for a single time constant eff (F·cm -2 ), so for CPE dl Related C eff Calculate the arc initiation resistance using the compatible arc initiation resistance of each sample studied. eff The effective thickness d of the innermost layer of the coating is calculated from the numerical value eff :
[0121]
[0122] Where ε0 is the dielectric constant of vacuum (ε0 = 8.85 × 10 -14 F cm -1 ), A is the exposure test area (1cm 2 ), d eff (nm) is the effective thickness. eff (nm) is the thickness of the corrosion product film. In the NaCl solution system, the corrosion process of the AZ91D magnesium alloy substrate and its coating sample is essentially the reaction between H2O and Mg, so the corrosion product is mostly Mg(OH)2, with a small amount of MgO. Therefore, the dielectric constant ε of the corrosion product is (ε Mg(OH)2 =8.2).
[0123] In addition, in order to comprehensively evaluate the protective performance of the samples from the perspective of the entire EEC system, R total To represent the total resistance associated with corrosion protection, the calculation formula is as follows:
[0124] R total =R i +Rf +R ct ;
[0125] Table 2
[0126]
[0127]
[0128] Table 3
[0129] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 <![CDATA[C eff,i (F·cm -2 )]]> <![CDATA[4.44×10 -9 ]]> <![CDATA[4.81×10 -9 ]]> <![CDATA[3.06×10 -10 ]]> <![CDATA[4.73×10 -6 ]]> / <![CDATA[C eff,f (F·cm -2 )]]> <![CDATA[8.96×10 -10 ]]> <![CDATA[1.05×10 -9 ]]> <![CDATA[1.06×10 -9 ]]> <![CDATA[7.01×10 -10 ]]> <![CDATA[1.32×10 -5 ]]> <![CDATA[C eff,dl (F·cm -2 )]]> <![CDATA[1.41×10 -6 ]]> <![CDATA[9.16×10 -8 ]]> <![CDATA[1.80×10 -6 ]]> <![CDATA[2.51×10 -6 ]]> <![CDATA[9.51×10 -7 ]]> <![CDATA[d eff,i (mm)]]> <![CDATA[1.66×10 -4 ]]> <![CDATA[1.51×10 -4 ]]> <![CDATA[2.37×10 -3 ]]> <![CDATA[1.53×10 -7 ]]> / <![CDATA[d eff,f (mm)]]> <![CDATA[8.10×10 -4 ]]> <![CDATA[6.94×10 -4 ]]> <![CDATA[6.86×10 -4 ]]> <![CDATA[1.03×10 -3 ]]> <![CDATA[5.51×10 -8 ]]> <![CDATA[R total ]]> <![CDATA[1.54×10 6 ]]> <![CDATA[3.64×10 6 ]]> <![CDATA[4.48×10 6 ]]> <![CDATA[3.28×10 6 ]]> 1621.7
[0130] from Figures 6-7 , Tables 2 to 3 show:
[0131] (1) Figure 6 (a) to (c) show the Nyquist diagram, Bode impedance diagram and Bode phase angle diagram of AZ91D of comparative example 1 and MCS40 of example 1, MCS60 of example 2, MCS80 of example 3 and MCS100 of example 4. The charge transfer in the Nyquist diagram is related to the arc radius of the capacitor reactance. Generally speaking, the larger the radius of the capacitor arc, the greater the resistance to electron transfer and the lower the electron exchange rate. For metal materials, a low electron exchange rate usually means a low corrosion rate and good corrosion resistance.
[0132] The Nyquist plot of AZ91D of comparative example 1 shows two capacitance loops, and the semicircle diameter of the capacitor is about 120Ω·cm 2 The semicircle diameters of Examples 1 to 4 and Comparative Example 1 are significantly increased, showing the excellent protective effect of the coating. Examples 1 to 4 present two capacitance loops at medium and low frequencies, corresponding to the double-layer structure in the SEM morphology. The capacitance loop at high frequencies is related to corrosion products, such as Figure 6 (a) As shown. In the Bode diagram, the phase angles in the low-frequency and high-frequency regions reflect the integrity and corrosion resistance of the film. Generally, the higher the impedance modulus |Z|, the better the corrosion resistance of the sample. Figure 6 It can be seen from b that the |Z| values of all embodiments are higher than AZ91D of comparative example 1, among which the |Z| values of MCS40, MCS60, MCS80 and MCS 100 of embodiments 1 to 4 are more than 3 orders of magnitude higher than that of AZ91D. Figure 6 (c) shows that in the entire measured frequency range, the phase angles of Examples 1 to 4 and Comparative Example 1 are all below 90°, indicating that the behavior of the capacitor is not completely ideal. In the low and high frequency bands, the phase angles of Examples 1 to 4 are higher than the AZ91D magnesium alloy substrate of Comparative Example 1, further proving the protective effect of the coating.
[0133] (2) By Figure 8It can be seen that the anti-corrosion performance is ranked as follows: Comparative Example 1 < Example 1 < Example 4 < Example 2 < Example 3, and the MCS80 of Example 3 performs best in anti-corrosion performance.
[0134] 3. Immersion and hydrogen evolution test
[0135] 3.1 Immersion test
[0136] (1) The immersion test is used to evaluate the continuous corrosion behavior of the sample. Under room temperature conditions, MCS40, MCS60, MCS80, MCS100 of Examples 1 to 4 and AZ91D of Comparative Example 1 are weighed, and the weighed MCS40, MCS60, MCS80, MCS100 of Examples 1 to 4 and AZ91D of Comparative Example 1 are immersed in a 3.5wt% NaCl solution. The samples are taken out at 0h, 24h, 72h, 120h, and 168h, rinsed with a high-pressure water gun filled with deionized water, and then treated again in an ultrasonic cleaning environment. The total immersion time is 168h. After each group of materials is air-dried at room temperature, optical photographs of their surfaces are taken, as shown in FIG. Fig.10 As shown, and weigh to obtain the weight loss Δm (unit: g);
[0137] The MCS60 of Example 2 after immersion for 168 hours was characterized by X-ray photoelectron spectroscopy. Fig.12 shown.
[0138] (2) The electrochemical workstation was used to perform continuous EIS tests to analyze the corrosion behavior of the samples after immersion for 12 h, 24 h, 48 h, 72 h, and 96 h. Figure 6 , Figure 7 The EIS data analysis is performed using the equivalent circuit (EEC) in Fig. 9 , as shown in Table 4 and Table 5.
[0139] 3.2 Hydrogen evolution test
[0140] In the hydrogen evolution test, hydrogen is produced by the cathode hydrogen evolution reaction, so the amount of hydrogen evolution can be used as an indicator of the sample dissolution rate. The funnel is inverted above the sample, and a 25mL dropper is connected to the end of the funnel. The corrosion rate of AZ91D magnesium alloy and coating samples in 3.5wt% NaCl solution is studied by collecting the volume of hydrogen. The sample mass loss rate (V G ) and hydrogen evolution rate (V H ) is calculated according to the following formula:
[0141]
[0142] Among them, M i represents the initial weight (in mg), M f represents the final weight (in mg), Hi represents the initial liquid level of the dropper (in mL), H f represents the final liquid level of the dropper (in mL), and A is the area of the immersion zone (in mm 2 ), T is the immersion time (h).
[0143] The total corrosion rate (CR1) is calculated from the weight loss in accordance with ASTM G1-03 "Standard Practice for Preparation, Cleaning and Evaluation of Corrosion Test Specimens" and is expressed in mm / year. For hydrogen evolution experiments, the total weight loss is calculated according to the conversion relationship (1 mL H2 gas = 0.001083 g consumed Mg). CR1 is determined by the following formula
[0144]
[0145] Where, Δm is the weight loss (g); A is the exposure area of the sample in the NaCl solution (cm 2 ); t is the total immersion time of the sample (h); ρ is the density of AZ91D magnesium alloy (1.82 g / cm 3 ), the result is as follows Fig.11 shown.
[0146] Table 4
[0147]
[0148]
[0149] Table 5
[0150]
[0151]
[0152] The results are as follows Figures 9-11 , as shown in Tables 4 and 5:
[0153] (1) Fig. 9 The Nyquist and Bode plots of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4, and AZ91D of Comparative Example 1 are shown. As the immersion time increases, the protective effect of the samples improves, which is mainly due to the accumulation of corrosion products in the coating channels, which effectively prevents the corrosive medium from further entering the substrate interface. In AZ91D of Comparative Example 1, as the immersion time increases, the inductance loop in the Nyquist plot gradually disappears ( Fig. 9 a), indicating that the pitting phenomenon is weakened. At the same time, in the Bode diagram, the increase in impedance modulus |Z| and phase angle in the low-frequency region also reflects the reduction in corrosion rate ( Fig. 9bc). The capacitance loop, |Z| value and phase angle of all coating samples increased significantly during the immersion process ( Fig. 9 do), further demonstrating the reduction in corrosion rate. This reduction in corrosion rate is related to the generation of corrosion products, which effectively block the contact between the corrosive medium and the substrate through the coating.
[0154] (2) In the long-term immersion of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4, and AZ91D of Comparative Example 1, the EIS data analysis was performed using Figure 6 (d) Figure 6 (e) Figure 7 From the Nyquist plot of the AZ91D sample in comparative example 1, it can be clearly observed that with the increase of immersion time, the inductive reactance disappears at the 48h test ( Fig. 9 a). Before the inductive reactance disappears, use Figure 6 (d) is used for fitting analysis of the equivalent circuit, and after the inductive reactance disappears, Figure 7 For Examples 1 to 4, the equivalent circuit is always used. Figure 6 (e) Fitting is performed. It can be seen from the fitting results in Table 5 that the total resistance of all samples increased after immersion, which indicates that the protective performance of the samples was further improved during the immersion process.
[0155] (3) The immersion test can intuitively reflect the corrosion behavior of the sample in 3.5wt% NaCl solution. After immersion, the MCS40 of Example 1, the MCS60 of Example 2, the MCS80 of Example 3, the MCS100 of Example 4, and the AZ91D of Comparative Example 1 showed obvious corrosion differences in the optical images ( Fig.10). AZ91D completely lost its metallic luster after immersion for 24 hours, and obvious corrosion spots appeared at the corners. As the immersion time increased, the area of the corrosion zone expanded significantly, showing a trend of spreading from the edge to the center. Corrosion spots were observed in MCS40, MCS60 and MCS100 after immersion for 48 hours, 96 hours and 24 hours, respectively, and these corrosion spots were concentrated at the corners. Over time, the corrosion area did not expand significantly. MCS80 did not show corrosion spots during the entire test, indicating that MCS80 has excellent corrosion durability. In addition, although pits were formed at the corners of MCS40, MCS60 and MCS80 after corrosion, these pits were filled with corrosion products during the subsequent immersion process, while the MCS100 sample did not have this phenomenon. This is most likely because the corrosive medium has not completely eroded the CaCO3 layer, and the corrosion product that fills the corrosion points is Mg(OH)2 generated on the Mg substrate. This phenomenon may be related to the increase in the deposition thickness of the CaCO3 coating caused by the high concentration of the mixed solution. Due to pitting during the corrosion process, the coating becomes loose and the local bonding force decreases, resulting in coating shedding.
[0156] (2) Combining the mass loss in the immersion test and the hydrogen release in the hydrogen evolution experiment can more accurately analyze the behavior of the sample during the continuous corrosion process. Fig.11 The mass loss data of MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, MCS100 of Example 4 and AZ91D of Comparative Example 1 in a 168h immersion test and the hydrogen release data in a hydrogen evolution test in a 3.5wt% NaCl solution are shown. Fig.11 c. The slope of the curve in the line graph represents the weight loss rate and hydrogen evolution rate of each group during the exposure time. The larger the slope, the stronger the corrosion reaction ( Fig.11 a and d). Fig.11 (b) and Fig.11 (e) shows the average mass loss rate and hydrogen evolution rate of each group within 168 h. The results show that the V G and V H The value is greater than that of the coating sample. This shows that MCS40 of Example 1, MCS60 of Example 2, MCS80 of Example 3, and MCS100 of Example 4 have better anti-corrosion performance than AZ91DAZ91D of Comparative Example 1. Fig.11 As shown in Figure 5, the corrosion rate calculated by the mass loss test is lower than the corrosion rate obtained by the hydrogen evolution test. This lower mass loss corrosion rate may be due to the incomplete removal of corrosion products and the error in the weighing process. The comparison of the results shows that the mass loss and hydrogen evolution values of MCS80 in Example 3 are the lowest, which indicates that the sample formed in the 80mM mixed solution has a better anti-corrosion performance.
[0157] (3) Fig.12 As shown in Figure 2, the XPS spectrum of the MCS60 coating sample surface after 168 hours of immersion is similar to Figure 4 The uncorroded sample was compared. In the full spectrum, the peak intensity of the Si 2p orbital in the immersed sample completely disappeared ( Fig.12 a). In addition, no characteristic peak of CaSiO3 was found in the fine spectrum of Ca 2p ( Fig.12 e). In the Si 2p fine spectrum, no obvious characteristic peaks appear ( Fig.12 f), which indicates that CaSiO3 has been dissolved during the immersion process. In contrast, the C 1s fine spectrum ( Fig.12 b) Metal carbides and O1s fine spectra ( Fig.12 c) The intensity of the characteristic peaks of metal oxides is enhanced. Only one peak appears in the Mg 1s and Ca 2p fine spectra, corresponding to the characteristic peaks of Mg(OH)2 and CaCO3, respectively ( Fig.12 d and e). Considering that it is difficult for CaCO3 to be generated in a 3.5wt% NaCl solution environment, it can be inferred that during the immersion process, the CaSiO3 on the surface of the coating sample was dissolved.
[0158] Test Example 2:
[0159] Optical photographs of the magnesium alloy double-layer composite coating materials obtained in Example 1 and Comparative Example 3 were taken, and SEM tests were performed. The results are as follows: Fig.13 (a) Fig.13 (b) In order to accurately analyze the difference between the two sample placement methods, the preparation process was simulated and analyzed using the fluent module of Workbench. The results are shown in Fig.13 (c) and Fig.13 (d) as shown.
[0160] Depend on Fig.14 We can get:
[0161] (1) Fig.13 (a) and Fig.13 (b) shows the optical photographs and SEM images of the magnesium alloy double-layer composite coating materials prepared in the 60 mM mixed solution obtained in Example 1 and Comparative Example 3. It can be clearly seen from the optical photographs that the vertically placed magnesium alloy double-layer composite coating material is black, which is the result of the reaction between the magnesium alloy substrate and water; while the surface of the horizontally placed magnesium alloy double-layer composite coating material is milky white, which indicates that CaCO3 and CaSiO3 are deposited on the AZ91D magnesium alloy substrate.
[0162] (2) In the SEM image, the surface of the sample prepared by placing it vertically is relatively flat, while the surface of the sample placed horizontally shows a disordered arrangement of particles. Figure 3 XRD, EDS analysis results and Figure 4 XPS analysis of the samples showed that the main components of the particles deposited in the vertically placed samples were CaCO3 and CaSiO3, while these substances were not deposited on the samples prepared in the vertical position. This phenomenon is directly related to the change in the flow direction of the fluid inside the reactor during the heating process.
[0163] (3) Fig.13 (c) and Fig.13 (d) shows the velocity vector diagrams of the two models. It can be clearly observed that there are vortices in the solution system under both placement methods, and the arrow points to the flow direction of the vortex. The precipitate flows with the vortex and falls on the surface of the sample and its surroundings when passing through the sample. The vertically placed sample directly blocks the vortex, causing the precipitate in the vortex to be pushed to the surroundings. It is difficult to deposit on the sample surface under the influence of gravity, so it is difficult to form a coating. The horizontally placed sample is just the opposite. Most of the precipitate is deposited on the sample surface, forming a film / block under high temperature conditions, forming a coating with protective properties.
[0164] Test Example 3:
[0165] 1. The mechanical analysis and transient structural analysis of the AZ91D magnesium alloy matrix of Comparative Example 1 and Comparative Example 2 at 190°C were performed using the Workbench structure transient structure module. The results are as follows: Fig.14 , 15 shown.
[0166] Depend on Fig.14 , 15 We can get:
[0167] During immersion, corrosion spots initially appear at the corners, such as Fig.10 In addition, during the coating formation process, under high temperature and long-time processing conditions, the coating may not completely wrap the sample.
[0168] The deformation and stress of the AZ91D magnesium alloy matrix without chamfering are concentrated at the corners ( Fig.14 a). In actual sample preparation and testing, samples usually do not show obvious deformation, while the deformation generated by simulation analysis is mainly used to offset the impact of stress concentration. Stress concentration makes the sample more fragile, and usually damage occurs in the stress concentration area. In order to reduce the impact of stress concentration on the sample, AZ91D is chamfered. The simulation results are as follows: Fig.14 (b) The comparison of the results shows that although the stress concentration phenomenon still exists at the corners of the sample after chamfering treatment, the stress value is significantly reduced. During the heating process, the maximum and average values of the total deformation of the sample without treatment are smaller than those of the sample with chamfering treatment ( Fig.15a), the maximum and average equivalent stress values are higher than those of the chamfered samples ( Fig.15 b). This indicates that the samples after chamfering are easier to deform and thus effectively resist stress concentration.
[0169] 2. Immersion test
[0170] Under normal temperature conditions, MCS40 of Example 5, MCS60 of Example 6, MCS80 of Example 7, MCS100 of Example 8, and AZ91D of Comparative Example 2 were immersed in a 3.5wt% NaCl solution. Each group of materials was taken out after 0h, 24h, 72h, 120h, and 168h, rinsed with a high-pressure water gun filled with deionized water, and then treated again in an ultrasonic cleaning environment. After each group of materials was air-dried at room temperature, optical photographs of their surfaces were taken, as shown in FIG. Fig.16 As shown;
[0171] Depend on Fig.16 We can get:
[0172] Immersion experiments were conducted to observe the corrosion conditions of each group, and the results verified the accuracy of the workbench simulation results.
[0173] Compared with the case before chamfering, the degree of corrosion is significantly reduced. The pitting of the corners of the AZ91D magnesium alloy substrate in Comparative Example 2 is significantly weakened, and the overall corrosion is more uniform than before chamfering. The MCS60 in Example 6 and the MCS100 in Example 8 had pitting at one corner due to poor polishing, while no corrosion spots appeared in the smooth chamfered area. These phenomena indicate that chamfering effectively reduces stress concentration and significantly improves the formation and performance of the coating.
[0174] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a magnesium alloy double-layer composite coating, characterized in that: The preparation method comprises the following steps: (1) polishing the magnesium alloy substrate to obtain a polished substrate, ultrasonically cleaning the polished substrate with ethanol, and then naturally drying to obtain a treated magnesium alloy substrate; (2) Na2SiO3 solution and Ca(HCO3)2 solution are mixed to obtain a mixed solution, wherein the concentration of Ca(HCO3)2 in the mixed solution is supersaturated; the treated magnesium alloy substrate is placed in the mixed solution, and subjected to hydrothermal treatment at 180°C to 200°C, followed by drying, to obtain a double-layer composite coating on the treated magnesium alloy substrate, namely, a magnesium alloy double-layer composite coating.
2. The method for preparing a magnesium alloy double-layer composite coating according to claim 1, characterized in that: The magnesium alloy substrate in step (1) is also chamfered before polishing.
3. The method for preparing a magnesium alloy double-layer composite coating according to claim 1, characterized in that: The total concentration of Na2SiO3 and Ca(HCO3)2 in the mixed solution is 40-100 mM.
4. The method for preparing a magnesium alloy double-layer composite coating according to claim 3, characterized in that: The volume ratio of the Na2SiO3 solution to the Ca(HCO3)2 solution is 1-2:1-2; the concentration of the Na2SiO3 solution is 40-100 mol / L; the concentration of the Ca(HCO3)2 solution is 40-100 mol / L.
5. The method for preparing a magnesium alloy double-layer composite coating according to claim 1, characterized in that: The time of the hydrothermal treatment in step (2) is 50 min to 70 min.
6. The method for preparing a magnesium alloy double-layer composite coating according to claim 5, characterized in that: The drying temperature in step (2) is 90° C. to 110° C., and the drying time is 50 min to 70 min.
7. The method for preparing a magnesium alloy double-layer composite coating according to claim 6, characterized in that: When the treated magnesium alloy substrate is placed in the mixed solution in step (2), the treated magnesium alloy substrate is placed horizontally in the mixed solution.
8. A magnesium alloy double-layer composite coating, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The magnesium alloy double-layer composite coating according to claim 8, characterized in that: The thickness of the composite coating is 50 μm to 1 mm.
10. An application of a magnesium alloy double-layer composite coating, characterized in that: The magnesium alloy double-layer composite coating according to any one of claims 8 to 9 is used for the protection of magnesium alloys.